DNA Polymerase in the Core of the Human Hepatitis B Virus Candidate - Robinson, William S. (1974)
Experiments were done to show that the human hepatitis B antigen (HBAg)-associated DNA polymerase is a component of Dane particles and their antigenically distinct cores prepared by Nonidet P-40 detergent treatment of Dane particles. Before detergent treatment, the DNA polymerase was precipitated by serum containing anti-HB surface antigen (anti-HB(s)) but not with serum containing anti-HB core antigen (anti-HB(c)). After detergent treatment, the enzyme was precipitated by anti-HB(c)- and not by anti-HB(s)-containing serum. Highly purified 16- to 25-nm HBAg particles blocked only the precipitation of DNA polymerase in untreated HBAg preparations. The 110S structure with which the DNA reaction product remains associated in Nonidet P-40-treated preparations was identified as Dane particle core by immunoprecipitation with serum containing anti-HB(c). The DNA polymerase and the radioactive DNA reaction product were used as markers for core in immunoprecipitation tests for anticore. In such assays, 8 of 11 human sera with anti-HB(s) activity and all of 10 sera from chronic HBAg carriers were found to contain anti-HB(c) activity.